Steel-aluminum transition joint and solid-phase deformation driven deposition manufacturing method thereof
By designing the SI micro -layer in the steel aluminum transition interface and the use of solid -oriented variable -driven deposition methods, the problem of being easily generated by steel and aluminum transition joints to generate crispy interclass compounds, and realizes the improvement of the force of the joints and the optimization of the production process.
Patent Information
- Application Number
- CN202411337421.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-25
Smart Images

Figure CN119347090A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a transition joint and a deposition manufacturing method thereof, belonging to the technical field of dissimilar material connection. Background Art
[0002] In many fields such as automobiles, ships, and aerospace, steel-aluminum composite structures are gradually replacing traditional all-steel structures to meet the design requirements of lightweight energy conservation and emission reduction. However, the huge difference in physical properties between steel and aluminum makes it difficult to connect them heterogeneously. In addition, due to the metallurgical reaction between aluminum and steel, a large amount of brittle intermetallic compounds (Fe 2 Al 5 , Fe 4 Al 13 etc.), which reduces the strength of the steel-aluminum transition interface, leading to the deterioration of the bearing performance of the entire joint.
[0003] Silicon (Si) atoms have a lower chemical potential at the steel-aluminum interface and tend to diffuse to the interface first. On the other hand, Si elements can effectively reduce the activity coefficient of aluminum atoms, thereby reducing the thickness of the diffusion layer between steel and aluminum metals. Therefore, the appropriate introduction of Si elements at the interface is conducive to controlling the thickness of the intermetallic compound at the interface, thereby improving the mechanical properties of the joint. In addition, the introduction of Si elements can change the structure of the intermetallic compound and generate Fe(Al,Si) with relatively better toughness. 2 Al 8 Si, etc., can effectively reduce joint stress and improve joint mechanical properties.
[0004] The solid phase deformation driven deposition method is developed from the stir friction welding technology. It realizes the thermal plasticization and deposition process of the material through a rotating stirring head with a threaded structure and a static material storage chamber. Since this process does not involve the melting and solidification of the material, it can effectively avoid defects such as pores and cracks in the steel-aluminum transition joint. In addition, due to the low heat input of this process, it can effectively control the thickness of the intermetallic compound and reduce the residual stress of the joint, thereby improving the mechanical properties of the joint. The solid phase deposition additive method can be used to more flexibly prepare steel-aluminum transition joints with different shape requirements with the idea of "point by point and layer by layer, breaking the whole into parts", which has a higher degree of freedom in production.
[0005] Therefore, by using the solid-phase deformation-driven deposition method and designing a Si-containing microlayer at the interface, the production and preparation of high-performance steel-aluminum transition joints with high degrees of freedom can be achieved, which has important application value in the automotive, shipbuilding and aerospace fields. Summary of the invention
[0006] The present invention aims to solve the problem that brittle intermetallic compounds are easily generated in steel-aluminum transition joints, resulting in deterioration of joint performance, and further proposes a steel-aluminum transition joint and a solid phase deformation driven deposition manufacturing method thereof.
[0007] The technical solution adopted by the present invention to solve the above problems is: the steel-aluminum transition joint of the present invention comprises a deposited aluminum alloy, a steel material and a Si-containing microlayer;
[0008] The deposited aluminum alloy and the steel are arranged in sequence from top to bottom, and the Si-containing microlayer is arranged between the deposited aluminum alloy and the steel.
[0009] The steps of the solid phase deformation driven deposition manufacturing method of the present invention include:
[0010] Step 1, preparing Si microlayer;
[0011] Step 2: Solid phase deformation driven deposition.
[0012] Further, in step 101, a steel material with a thickness of 1 to 50 mm is prepared, the oxide layer on the surface to be deposited is removed, and the oil and dust are cleaned;
[0013] Step 102: Using the Si-containing material as a raw material, the surface of the steel is enriched with Si, and a Si-containing microlayer with a thickness of about 5 to 500 μm is formed.
[0014] Furthermore, Si-enrichment methods include solid phase deformation driven deposition, stir friction deposition, hot dip plating, magnetron sputtering and silanization.
[0015] Furthermore, step 2 specifically includes:
[0016] Step 201, transmitting the wire material for preparing the steel-aluminum transition joint to a deformation driven deposition device through a wire feeding mechanism;
[0017] Step 202, the wire material entering the device is sheared and transported by the mutual movement between the tools in the device;
[0018] Step 203, achieving thermal plasticization of the material under the action of friction heat and large plastic deformation, and further completing the deposition process of the material;
[0019] Step 204: Various aluminum alloys are deposited on the steel with Si-rich surface by using the deformation driven deposition method, so that a variety of steel-aluminum transition joints can be prepared.
[0020] Furthermore, the Si-containing microlayer includes a pure Si layer, an Al-Si alloy layer, a Fe-Si alloy layer and a Fe-Al-Si alloy layer, and has a thickness of 5 to 500 μm.
[0021] Furthermore, a Si-containing aluminum alloy wire with a diameter of Φ1.2 to 3.0 mm is delivered to a deformation-driven deposition device through a wire feeding mechanism, and a Si-containing microlayer with a thickness of 100 to 500 μm is obtained at parameters of 300 to 1500 rpm and 10 to 200 mm / min.
[0022] The beneficial effects of the present invention are:
[0023] 1. The present invention designs a Si-containing microlayer at the steel-aluminum transition interface, regulates the interface metallurgical reaction, improves the types of intermetallic compounds at the interface, avoids the formation of brittle intermetallic compounds, reduces the residual stress of the joint, and controls the thickness of the Si-containing layer to strengthen the steel-aluminum interface while ensuring the overall mechanical properties of the joint, thereby improving the mechanical properties of the joint;
[0024] 2. The solid phase deformation driven deposition method promotes dynamic recovery and recrystallization of the material through large plastic deformation, realizes ultrafine crystallization or even nanocrystallization of the grain structure, and forms an ultra-dense deposited aluminum alloy with extremely low porosity under the forging action of the lower end face of the static storage cavity, thereby ensuring the overall mechanical properties of the steel-aluminum joint;
[0025] 3. The deformation-driven deposition method can realize the “breaking down of the steel-aluminum transition joint into parts”. The steel-aluminum transition joint is prepared by the point-by-point and layer-by-layer deposition method. Therefore, it has a higher degree of freedom in structural design and can realize the preparation of joints of various shapes and sizes. In addition, this method has the characteristics of geothermal input, which can effectively control the growth of intermetallic compounds, reduce the residual stress of the joint, and is conducive to improving the mechanical properties of the joint.
[0026] 4. The ultrafine grain structure obtained by introducing Si-containing microlayers at the interface and deformation-driven deposition method can break through the technical bottleneck of high-reliability steel-aluminum transition joints. This method does not involve the melting-resolidification process, which significantly reduces the energy required for the production of steel-aluminum transition joints, reduces the process difficulty, and avoids the defects caused by the melting-solidification process. It is a green manufacturing technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the structure of the T-shaped steel-aluminum transition joint containing Si microlayers according to the present invention;
[0028] Figure 2 This is a schematic diagram of the structure of the annular steel-aluminum transition joint containing Si microlayers according to the present invention;
[0029] Figure 3 It is a schematic diagram of the structure of the tubular steel-aluminum transition joint containing Si microlayers according to the present invention;
[0030] Figure 4 is a schematic diagram of the deformation driven deposition method of the present invention;
[0031] Figure 5 It is a schematic diagram of the structure of the stirring head and the static material storage chamber described in the present invention.
[0032] Figures 1 to 5 In the figure, 1-deposited aluminum alloy, 2-steel, 3-Si-containing microlayer, 4-deformation driven deposition device, 401-stirring head, 402-storage chamber, 40101-clamping part, 40102-threaded part, 4010-stirring needle, 40201-wire feeding hole, 40102-lower end surface, 403-wire, 404-wire feeding mechanism. DETAILED DESCRIPTION
[0033] Specific implementation method 1: Figures 1 to 3 As shown, a steel-aluminum transition joint comprises a deposited aluminum alloy (1), a steel material (2) and a Si-containing microlayer (3);
[0034] The deposited aluminum alloy (1) and the steel material (2) are arranged in sequence from top to bottom, and the Si-containing microlayer (3) is arranged between the deposited aluminum alloy (1) and the steel material (2).
[0035] Specific implementation method 2: Figure 4 and Figure 5 As shown, a solid phase deformation driven deposition manufacturing method for the steel-aluminum transition joint as claimed in the claim, the specific steps include:
[0036] Step 1, prepare steel with a thickness of 1 to 50 mm, remove the oxide layer on the surface to be deposited and clean the oil and dust; use Si-containing material as raw material, and prepare Si-containing microlayer by surface Si-enriching methods such as solid phase deformation driven deposition, stir friction deposition, hot dip plating, magnetron sputtering or silanization, and form a Si-containing microlayer with a thickness of about 5 to 500 μm on the surface of steel 2;
[0037] Step 2: The wire 403 for preparing the steel-aluminum transition joint is transmitted to the deformation-driven deposition device 4 through the wire feeding mechanism 404. The wire 403 entering the device realizes the shearing and transportation process of the material through the mutual movement between the tools in the device; the material is thermally plasticized under the action of friction heat and large plastic deformation, and the deposition process of the material is further completed. By using this deformation-driven deposition method to deposit various aluminum alloys on the steel 2 having a Si-containing microlayer, a variety of steel-aluminum transition joints can be prepared.
[0038] The deformation driven deposition device 4 is composed of a rotating stirring head 401 and a stationary material storage chamber 402 matched therewith.
[0039] Specific implementation method 2: Figures 1 to 3As shown, the steel material 2 is one of non-alloy steel, low alloy steel, alloy steel and stainless steel, and its length is 10 mm to 1000 mm.
[0040] Specific implementation method three: Figures 1 to 3 As shown, the Si-containing layer 3 is one of a pure Si layer, an Al-Si alloy layer, a Fe-Si alloy layer and a Fe-Al-Si alloy layer, and has a thickness of 5 to 500 μm.
[0041] Specific implementation method four: Figures 1 to 3 As shown, the deposited aluminum alloy 1 is one of Al-Cu alloy, Al-Mg alloy, Al-Si alloy, and Al-Zn-Mg-Cu alloy.
[0042] Specific implementation method five: Figure 4 and Figure 5 As shown, the Si-containing materials described in the preparation method of the Si-containing microlayer 3 structure include but are not limited to Si-containing aluminum alloys, silane treatment agents and pure Si; the Si-containing materials can be selected from various forms of raw materials such as wire, powder, silane and solution according to different surface Si-enrichment methods.
[0043] Specific implementation method six: Figure 4 and Figure 5 As shown, the surface Si-enriching method described in the preparation method of the Si-containing microlayer 3 structure includes but is not limited to deformation driven deposition, stir friction deposition, hot dip plating, magnetron sputtering and silanization methods;
[0044] Among them, the Si-enriching method can realize the preparation of Si-containing microlayers with Si content of 1 to 100% and thickness of 5 to 500 μm.
[0045] Specific implementation method seven: Figure 4 and Figure 5 As shown, the solid phase deformation driven deposition method described in the preparation method of the Si-containing microlayer 3 structure transmits the Si-containing aluminum alloy wire with a diameter of Φ1.2 to 3.0 mm to the deformation driven deposition device 4 through the wire feeding mechanism 404 and obtains the Si-containing microlayer 3 with a thickness of 100 to 500 μm at the parameters of 300 to 1500 rpm and 10 to 200 mm / min.
[0046] Specific implementation method eight: Figure 4 and Figure 5 As shown, the friction stir deposition method described in the preparation method of the Si-containing micro-layer 3 structure uses the Si-containing aluminum alloy rod to achieve the process of thermal plasticization and deposition by utilizing the friction heat and large plastic deformation process between the Si-containing aluminum alloy rod and the surface of the steel material 2;
[0047] Wherein, the Si-containing microlayer 3 with a thickness of 100 to 500 μm can be achieved at the parameters of 200 to 2000 rpm and 10 to 200 mm / min.
[0048] Specific implementation method nine: Figure 4 and Figure 5 As shown, the hot dip plating method described in the preparation method of the Si-containing microlayer 3 structure pickles, degreases, rinses and dries the surface of the steel material 2, and then a Si-containing plating solution can be selected and dip-plated in a protective gas.
[0049] Among them, it can be heated to 750-800℃ at a speed of 5-20℃ / s and kept warm for 80-150s, then cooled to a dipping temperature of 0-5℃ or above at a cooling rate of 5-20℃ / s to start dipping, and then cooled to room temperature at a speed of 10-25℃ / s after dipping.
[0050] Specific implementation method ten: Figure 4 and Figure 5 As shown, the magnetron sputtering method described in the preparation method of the Si-containing microlayer 3 structure can use single crystal Si or FeSi alloy as raw material, the target material diameter is 50-70 mm, the thickness is 3-4 mm, and the target-substrate distance is 25-35 mm. Under the working pressure of 0.5-1 Pa, the target material is 4.6-5.0 W·cm -2 The power density is deposited on the surface of steel 2.
[0051] Specific implementation method eleven: Figure 4 and Figure 5 As shown, the rotating stirring head 401 is composed of a clamping portion 40101, a threaded portion 40102 and a stirring needle 40103 at the end. The threaded structure of the threaded portion 40102 can realize the shearing and transmission process of the material, and the stirring needle 40103 at the end can enhance the material flow behavior between different deposition layers and achieve good bonding between the deposition layers.
[0052] Specific implementation method 12: Figure 4 and Figure 5 As shown, the static material storage chamber 402 and the rotating stirring head 401 should cooperate with each other, and a clearance fit is satisfied between the two, and the clearance is 0.2-1.0 mm.
[0053] The material storage chamber 402 has two structures, namely a wire feeding hole 40201 and a lower end surface 40202 . The lower end surface 40202 can exert a forging effect on the newly deposited material, which is beneficial to optimizing the structure of the deposited material and improving its performance.
[0054] Specific implementation method thirteen: Figure 4 and Figure 5As shown, the material deposition process can use aluminum alloy wire with a diameter of Φ1.2-3.0 mm, and obtain a dense aluminum alloy deposition layer 3 with a single layer thickness of 1.0-2.0 mm at parameters of 300-1500 rpm and 100-1000 mm / min.
[0055] Specific implementation method 14: Figure 4 and Figure 5 As shown, the material deposition process can select aluminum alloy rods with a diameter of Φ10-30 mm, and obtain a dense aluminum alloy deposition layer 3 with a single layer thickness of 1.0-4.0 mm under the parameters of 300-1500 rpm and 100-1000 mm / min.
[0056] Example
[0057] Embodiment 1:
[0058] This embodiment uses a steel-aluminum transition joint and a solid phase deformation driven deposition manufacturing method thereof in the following steps:
[0059] 1. Preparation of Si-containing microlayer structures
[0060] Prepare 316L stainless steel with a thickness of 1 to 50 mm, remove the oxide layer on the surface to be deposited and clean it. Take 4043 aluminum alloy wire with a diameter of Φ1.2 to 3.0 mm as the raw material, and send the wire to the deformation-driven deposition device (consisting of a rotating stirring head and a static storage chamber) through the wire feeding mechanism, and realize the shearing, thermal plasticization and deposition process in the device. Under the deposition parameters of 600rpm-50mm / min, a Si-containing deposition layer with a thickness of about 500μm is formed on the steel surface.
[0061] 2. Deformation Driven Deposition Method
[0062] The 2219 aluminum alloy wire with a diameter of Φ2.4mm is transmitted to the deformation-driven deposition device (consisting of a rotating stirring head and a static storage chamber) through the wire feeding mechanism, and the shearing, thermoplasticization and deposition processes are realized in the device. The travel speed is 450rpm-150mm / min, and the thickness of the deposited layer is 1.6mm. The stirring needle at the bottom of the stirring head is 2mm long and the root diameter is 4mm. The depth of the stirring needle penetrating into the 4043 aluminum alloy layer is 0.4mm. Under the action of the stirring needle, the 4043 aluminum alloy and the 2219 aluminum alloy are fully mixed to improve the joint performance.
[0063] Embodiment 2:
[0064] This embodiment uses a steel-aluminum transition joint and a solid phase deformation driven deposition manufacturing method thereof in the following steps:
[0065] 1. Preparation of Si-containing microlayer structures
[0066] The surface of the 40Cr steel to be deposited was ground and polished, then rinsed with deionized water and ultrasonically cleaned with alcohol, and then immersed in a sodium hydroxide solution for 6 min. After rinsing with clean water, it was immersed in a 15% HCl solution for 2 min. After deionized water and alcohol cleaning, it was heated at 88 °C and 5% K 2 ZF 6 The steel surface was assisted by plating in aqueous solution, and then dried in a drying oven at 120℃ / h for 60s. Anodizing was performed in 175g / L sulfuric acid + 7g / L oxalic acid electrolyte, and finally the steel surface was silanized using KH560 silane treatment agent in a mixed solution of 6mL KH560 + 20mL anhydrous ethanol + 75mL deionized water at 70℃ for 5min, and finally a silane layer with a thickness of about 20μm was obtained.
[0067] 2. Deformation Driven Deposition Method
[0068] The 7075 aluminum alloy rod with a diameter of Φ20mm is transferred to the stir friction deposition device (composed of a hollow stirring head) through the wire feeding mechanism, and the heat is plasticized and the deposition process is completed under the action of friction heat and large plastic deformation with the surface of the steel plate. The thickness of the first deposition layer is 2.0mm, and the deposition parameters are 700rpm-225mm / min. The stirring needle at the bottom of the stirring head is 2.0mm long and the root diameter is 4mm. The stirring needle is in micro-contact with the Si-containing microlayer on the steel surface. The single layer thickness of the subsequent deposition process is 1.8mm, the parameters are 700rpm-250mm / min, and the stirring needle penetrates 0.2mm into the previous layer.
[0069] Embodiment 3:
[0070] This embodiment uses a steel-aluminum transition joint and a solid phase deformation driven deposition manufacturing method thereof in the following steps:
[0071] 1. Preparation of Si-containing microlayer structures
[0072] Prepare low silicon steel with a thickness of 3mm, grind and polish the surface, and remove the oxide layer and oil stains on the surface to be deposited. Use N-type single crystal Si wafer with a diameter of 60mm and a thickness of 3.5mm, and the target-substrate distance is 30mm. Under the working pressure of 0.8Pa, the target is 4.86W·cm -2 The power density of the sample was 2000 W / m and the sample was placed in a vacuum heat treatment furnace for diffusion treatment. Finally, a pure Si film with a thickness of about 5 μm was obtained.
[0073] 2. Deformation Driven Deposition Method
[0074] The pure aluminum wire with a diameter of Φ2.4mm is transmitted to the deformation-driven deposition device (consisting of a rotating stirring head and a static storage chamber) through the wire feeding mechanism, and the shearing, thermoplasticization and deposition processes are realized in the device. The thickness of the first deposition layer is 2.0mm, and the deposition parameters are 1200rpm-450mm / min. The stirring needle at the bottom of the stirring head is 2.0mm long and the root diameter is 4mm. The stirring needle is in micro-contact with the Si-containing microlayer on the steel surface. The single layer thickness of the subsequent deposition process is 1.6mm, the parameters are 1200rpm-600mm / min, and the stirring needle penetrates 0.4mm into the previous layer.
[0075] Embodiment 4:
[0076] This embodiment uses a steel-aluminum transition joint and a solid phase deformation driven deposition manufacturing method thereof in the following steps:
[0077] 1. Preparation of Si-containing microlayer structures
[0078] The surface of 22MnB5 hot-formed steel is ground and polished, and then cleaned to remove surface oxides and oil stains. 2 +5%H 2 The protective gas was used, and a 90% Al-10% Si plating solution was selected. The solution was heated to 780°C at a rate of 10°C / s and kept at that temperature for 120s. Then, the solution was cooled to 5°C above the plating temperature at a rate of 10°C / s and then the plating was started. After the plating, the solution was cooled to room temperature at a rate of 20°C / s. Finally, a Si-containing microlayer with a thickness of about 50μm was obtained.
[0079] 2. Deformation Driven Deposition Method
[0080] The Al-7Mg alloy wire with a diameter of Φ1.6mm is transmitted to the deformation-driven deposition device (consisting of a rotating stirring head and a static storage chamber) through the wire feeding mechanism, and the shearing, thermoplasticization and deposition processes are realized in the device. The thickness of the first deposition layer is 2.0mm, and the deposition parameters are 600rpm-225mm / min. The stirring needle at the bottom of the stirring head is 2.0mm long and the root diameter is 4mm. The stirring needle is in micro-contact with the Si-containing microlayer on the steel surface. The single layer thickness of the subsequent deposition process is 1.6mm, the parameters are 600rpm-300mm / min, and the stirring needle penetrates 0.4mm into the previous layer.
[0081] Embodiment 5:
[0082] The surface of 316L stainless steel with a thickness of 15mm was ground and polished, and then cleaned to remove oxides and oil stains on the surface. The Al-Si alloy wire with a diameter of Φ2.4mm was transmitted to the deformation-driven deposition device (consisting of a rotating stirring head and a static storage chamber) through the wire feeding mechanism, and the shearing, thermoplasticization and deposition processes were realized in the device. The thickness of the first deposition layer was 1.2mm, and the deposition parameters were 400rpm-120mm / min. The stirring needle at the bottom of the stirring head was 1.2mm long and the root diameter was 2mm. The stirring needle was in micro-contact with the steel surface. The single layer thickness of the subsequent deposition process was 1.0mm, the parameters were 400rpm-100mm / min, and the stirring needle penetrated 0.2mm into the previous layer.
[0083] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent replacement and improvement made to the above embodiments without departing from the content of the technical solution of the present invention, based on the technical essence of the present invention, within the spirit and principles of the present invention, still fall within the protection scope of the technical solution of the present invention.
Claims
1. A steel-aluminum transition joint, characterized in that: It comprises a deposited aluminum alloy (1), a steel material (2) and a Si-containing microlayer (3); The deposited aluminum alloy (1) and the steel material (2) are arranged in sequence from top to bottom, and the Si-containing microlayer (3) is arranged between the deposited aluminum alloy (1) and the steel material (2).
2. A solid phase deformation driven deposition manufacturing method for the steel-aluminum transition joint according to claim 1, characterized in that: Specifically include: Step 1, preparing a Si microlayer (3); Step 2: Solid phase deformation driven deposition.
3. The solid phase deformation driven deposition manufacturing method of a steel-aluminum transition joint according to claim 2 is characterized in that: Step 1 specifically includes: Step 101, prepare steel (2) with a thickness of 1 to 50 mm, remove the oxide layer on the surface to be deposited and clean the oil and dust; Step 102: Using Si-containing material as raw material, the surface of the steel (2) is enriched with Si, and a Si-containing microlayer with a thickness of about 5 to 500 μm is formed.
4. The solid phase deformation driven deposition manufacturing method of a steel-aluminum transition joint according to claim 3 is characterized in that: The methods of Si enrichment include solid phase deformation driven deposition, stir friction deposition, hot dip plating, magnetron sputtering and silanization.
5. The solid phase deformation driven deposition manufacturing method of a steel-aluminum transition joint according to claim 2 is characterized in that: Step 2 specifically includes: Step 201, transmitting the wire material (403) for preparing the steel-aluminum transition joint to the deformation driven deposition device (4) through the wire feeding mechanism (404); Step 202, the wire (403) entering the device realizes the shearing and transportation process of the material through the mutual movement between the tools in the device; Step 203, achieving thermal plasticization of the material under the action of friction heat and large plastic deformation, and further completing the deposition process of the material; Step 204: Various aluminum alloys are deposited on the steel material (2) with a surface Si-rich treatment by using the deformation driven deposition method, thereby enabling the preparation of a variety of steel-aluminum transition joints.
6. The solid phase deformation driven deposition manufacturing method of a steel-aluminum transition joint according to claim 2 is characterized in that: The Si-containing microlayer (3) includes a pure Si layer, an Al-Si alloy layer, a Fe-Si alloy layer and a Fe-Al-Si alloy layer, and has a thickness of 5 to 500 μm.
7. The solid phase deformation driven deposition manufacturing method for a steel-aluminum transition joint according to claim 2 is characterized in that: A Si-containing aluminum alloy wire (403) with a diameter of Φ1.2 to 3.0 mm is delivered to a deformation-driven deposition device (4) through a wire feeding mechanism (404), and a Si-containing microlayer (3) with a thickness of 100 to 500 μm is obtained at parameters of 300 to 1500 rpm and 10 to 200 mm / min.
Citation Information
Patent Citations
Friction deformation-triggered self-propagating assistant aluminum / steel friction stirring overlapping method
CN105945419A
Welding method of aluminum-plated steel-aluminum alloy
CN111347160A
Processing technology of aluminum / steel composite transition joint
CN114310167A
Device and method for manufacturing dissimilar metal welding transition joint through solid-phase additive manufacturing
CN115673526A
Aluminum alloy-high-entropy alloy transition joint and friction stir welding method thereof
CN117020391A